PEMANFAATAN PROBIOTIK GUNA PENINGKATAN KUALITAS TELUR PUYUH - Kalsum, Umi; Rahardjo, Liliek; Wadjdi, Muhammad Farid (JURNAL RISET AGRIBISNIS & PETERNAKAN, 2016)
This study was conducted to ascertain the effect of adding probiotic into feed on the quality of quail’s eggs. Lactobacillus salivarius encapsulation (Ls encaps) was used as probiotic. A randomized block design was used to assign four levels of Ls encaps administration, that is P0 = Standard feed without Ls encaps, P1 = P0 + 107 cells/g Ls encaps, P2 = P0 + 108 cells/g Ls encaps and P3 = P0 + 109 cells/g Ls encaps. The results showed that adding Ls encaps did not alter significant egg quality (egg weight, the level protein of egg, and egg shell) but it significantly lowered cholesterol content in egg. In conclusion, L. Salivarius encaps may be used as a feed additive in quail diets to reduce egg cholesterol content.43.85 %, respectively. In conclusion, Ls encaps may be used as a feed additive for quail to enhance egg quality leading to improve our health. Keywords: probiotic, egg quality, cholesterol and quail.